Angioembolization of Scrotal Arteriovenous Malformations: A Case Report and Literature Review - Ammar Mohammad; Wael Sahyouni; Taisser Almeree; Bayan Alsaid (Case Reports in Vascular Medicine)
Arteriovenous malformations (AVMs) of the scrotum are rare lesions, usually diagnosed incidentally during the evaluation of scrotal masses or infertility. It could be presented with acute bleeding or acute pain. We are presenting a case of painless bilateral infiltrated scrotal mass (more advanced in the left side) developed dramatically over a year, no other symptoms existed. The diagnosis was made using duplex ultrasound (DUS), computed tomography arteriography (CTA), and digital subtraction angiography (DSA). Three sessions of angioembolization were performed and followed by surgical resection of the left side of the scrotum.